Persepsi Pengunjung Terhadap Keindahan, Kenyamanan, dan Keamanan Pada Lapangan Arga Coka Pegok Kota Denpasar - Trihartady, Bayu; Semarajaya, Cokorda Gede Alit; Sukewijaya, I Made (Jurnal Arsitektur Lansekap, 2024)
Visitors Perception of Beauty, Comfort and Security at Arga Coka Pegok Field, Denpasar City. Arga Coka Field is a field located in Denpasar City with an area of 13.334 m2. Arga Coka field has a main function as a soccer field by supporting other sports activities and as a means of recreation for both parents and children. The purpose of this study was to determine the visitor's perception of the beauty, comfort, safety of the Arga Coka Field so as to provide input to the manager to improve the quality of the site. The research method used is a survey method. Data were collected in the form of primary data through field observations, interviews, questionnaires and secondary data in the form of literature studies. Based on the research conducted, it was found that the visitor's perception of the beauty of the Arga Coka Field is quite beautiful, but there are some parts of the field that according to visitors are not as beautiful as the parking area. Visitors' perceptions of comfort at Arga Coka Field are quite comfortable, the convenience of the parking area needs to be improved because the majority of visitors feel uncomfortable. Visitors' perception of security at Arga Coka Field is quite safe. According to the perception of visitors, the cleanliness of the Arga Coka Field, the majority of visitors stated that it was not clean and needed attention from the management because cleanliness would affect the beauty and comfort of visitors. Suggestions from this study are managers need to improve cleanliness, supervision and improve existing facilities at Arga Coka Field.